Selected trace element concentrations in peat used for cosmetic production - a case study from southern Poland = Koncentracja wybranych pierwiastków śladowych w torfie wykorzystywanym w przemyśle kosmetycznym - studium przypadku z Polski południowej - Glina, Bartłomiej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the study was to assess the concentration of selected trace elements in organic soils used as a source to obtain a unique peat extract for cosmetics production. Peat material for laboratory analysis were collected from fen peatland located in the Prosna River Valley (Borek village). Studied peatland is managed by ?Torf Corporation? company as a source of material to obtain peat extract for cosmetics production.
Keywords: fen peatland; peat extraction; cosmetic industry; heavy metals; torfowiska niskie; eksploatacja; przemysł kosmetyczny; metale ciężkie